2018
DOI: 10.1093/ibd/izy027
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Anthropometrics of Children With Inflammatory Bowel Disease: A Comparison With the General Population

Abstract: The diet of children with IBD differs from the general pediatric population, with lower energy intake and high rates of food avoidance. Evaluation of the dietary intake alongside anthropometrics may be important to prevent nutrition deficiencies and promote health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 63 publications
4
16
0
Order By: Relevance
“…The study was not designed to explore the perceived effects of macronutrients; however, from the other responses received, 8% of participants specified foods with a high fat content, and 5% specified takeaways or deep-fried foods. These findings are in agreement with previous and current studies where patients with IBD have identified fast food [ 35 , 48 ], fatty food [ 15 , 17 , 34 , 36 , 37 ], fried and fatty foods [ 14 ], deep-fried and fatty food [ 16 , 39 ], oily food [ 38 ], and fatty meats [ 58 ] in symptom onset or exacerbation. Furthermore, evaluation of dietary intake changes in over 4200 families in Japan over two decades found positive associations between increasing CD incidence and total fat, animal fat, and omega-6 fatty acids [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study was not designed to explore the perceived effects of macronutrients; however, from the other responses received, 8% of participants specified foods with a high fat content, and 5% specified takeaways or deep-fried foods. These findings are in agreement with previous and current studies where patients with IBD have identified fast food [ 35 , 48 ], fatty food [ 15 , 17 , 34 , 36 , 37 ], fried and fatty foods [ 14 ], deep-fried and fatty food [ 16 , 39 ], oily food [ 38 ], and fatty meats [ 58 ] in symptom onset or exacerbation. Furthermore, evaluation of dietary intake changes in over 4200 families in Japan over two decades found positive associations between increasing CD incidence and total fat, animal fat, and omega-6 fatty acids [ 59 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, 55% of participants reported an association between dietary elements and the onset of their IBD symptoms, consistent with the range of 33–68% observed in other studies [ 15 , 17 , 32 , 33 , 34 ]. Moreover, within the range seen in other studies (44–76.5%) [ 32 , 34 , 35 , 36 , 37 , 38 ] a greater percentage of participants (70%) reported an association between diet and symptom exacerbation.…”
Section: Discussionsupporting
confidence: 79%
“…Finally, despite a low consumption in fibers, as previously reported [ 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] and the low-intermediate adherence to MD reported in our IBD patients, we found a significant inverse correlation between adherence to MD and fecal calprotectin. Associations between nutrients and inflammation have been established [ 30 ].…”
Section: Discussionsupporting
confidence: 63%
“…On the contrary, a more recent pediatric study from Dierden at al. found that the diet of children with IBD differs from the general pediatric population, with lower energy intake [ 24 ]. More specifically, protein intake did not differ, while fat intake was higher in pediatric IBD and carbohydrate intake was lower.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies are focused on the role of diet in the aetiology of the disease rather than the current nutrition of the patients, recent research has shown that paediatric IBD patients have a higher fat intake than healthy subjects [8]. Prior to that, Silva et al also reported a deficiency in the intake of energy and many micronutrients, while the consumption of fats and sweets were higher than recommended [9].…”
Section: Introductionmentioning
confidence: 99%